Factors supporting the transition to a "green" European economy and funding mechanisms - Dan Costin Nitescu; Valentin Murgu (Amfiteatru Economic Journal, 2022)
The transition from fossil fuels to fuels from renewable energy sources can lead to decentralisation of the energy systems, causing structural changes in economic and political relations between countries. The economy of the energy transition will change the global economic map. The move to the "new" "green" European Economy can be achieved in a sustainable way, as long as, certain catalysts are identified and appropriate financial support mechanisms are anchored. This research paper addresses the issue of identifying such factors that, being aggregated, can support the complex process of transition to a new economy. The case study of the research proposes a specific methodology for the analysis of exogenous factors: the energy consumption from fossil fuels, the consumption of renewable energy, the number of researchers involved in research and development (generically assimilated to innovation), and the value of domestic credit to the private sector. The influences of exogenous factors on two endogenous factors are analyzed: Gross Domestic Product and exports of goods and services, representative of the economic dimension, at the level of selected countries in the European Union. The results obtained show that all four independent variables significantly influence the economic performance of selected countries in the European Union, analyzed in terms of Gross Domestic Product and exports of goods and services. The significant impact of energy consumption from renewable sources is noticeable. The research also includes a dedicated section to correlate the results of the empirical study with the financial dimension of the instruments developed to support the energy transition.
Keywords: C23; O11; O47; O52; 330; economy of the European Union; exports of goods and services; financial mechanisms; Gross Domestic Product (GDP); renewable energy; research and development